Analisis Peran Kepemimpinan Birokrasi dan Kedisiplinan Kerja untuk Meningkatkan Kinerja Pegawai Dinas Perindustrian dan Perdagangan Provinsi Jambi - Dea Ola Hotma Sari Aritonang; Hendriyaldi Hendriyaldi; Fitri Widiastuti (Ebisnis Manajemen, 2025)
This study was conducted with the aim of understanding and analyzing the role of bureaucratic leadership and work discipline in improving the performance of employees at the Jambi Province Department of Industry and Trade. This study uses a quantitative method with data collection techniques by distributing questionnaires to 85 respondents who are civil servants at the Industry and Trade Office of Jambi Province, with sampling conducted using the census technique. The data analysis techniques in this study used Multiple Regression Test, t-test, F-test, and Coefficient of Determination (R2) using the IBM SPSS Statistics 25 program. The results of this study indicate that, partially, the variable of bureaucratic leadership has a positive and significant effect on improving employee performance. Partially, work discipline also has a positive and significant influence on employee performance. Collectively or simultaneously, bureaucratic leadership and work discipline have a positive and significant effect on employee performance. The better the bureaucratic leadership and the higher the work discipline of employees, the better the performance of the employees at the Jambi Provincial Department of Industry and Trade.